The Plan-Do-Check-Action Approach Model for Quality Management in Community Learning Activity Centers - Wiharjo, Suyadi Murdi; Wulandari, Dian (Indo Consultan Energi, 2023)
Quality management is essential for the Center for Community Learning Activities (PKBM) as an entity that runs out-of-school education programs in packages A, B and C. One approach to quality management is the Plan-Do-Check-Action (PDCA) model. This study aims to describe the PDCA model for PKBM quality management. The method used in this study is qualitative, with a descriptive approach and a literature study. Data were obtained from Google Scholar reference journal articles in the 2011-2022 publication period. Articles were searched using the Publish or Perish application with the